Case Report: Idiopathic Traumatic Neuroma of the Gallbladder Without Previous Surgery - Lin, Tianyu; Bissessur, Abdul Saad; Zhu, Yingjie; Fukuyama, Teruko; Ding, Guoping; Cao, Liping (Frontiers in Surgery, 2022)
Traumatic neuroma mostly results from nerve injury caused by surgery or trauma. Traumatic neuroma of gallbladder without prior abdominal surgery is extremely rare and we termed it as "idiopathic traumatic neuroma of gallbladder". Due to its rarity and a lack of specific clinical and radiological features, it is most commonly misdiagnosed. In our case, the patient was admitted at our hospital for cholangiocarcinoma. Repeated abdominal contrast-enhanced computed tomography scans preoperatively indicated hilar cholangiocarcinoma. Due to insufficient future liver remnant, we planned preoperative percutaneous transhepatic cholangiodrainage (PTCD) and percutaneous transhepatic portal vein embolization (PVE) based on multidisciplinary team consultation. The patient was then admitted 1 month later for surgery. We performed cholecystectomy and extensive right hepatectomy as gallbladder carcinoma was highly suspected intraoperatively. However, the final diagnosis was traumatic neuroma of gallbladder confirmed by pathological examination. Traumatic neuroma of gallbladder is very rare, and we hope to provide some references for diagnosis by reporting our case and reviewing the literature on this topic so that extensive treatment can be avoided, thus improving patients’ quality of life. To the best of our knowledge, this is the first reported case of traumatic neuroma without prior surgery in the English literature since 1996.